KARAKTERISTIK BATU BATA TANPA PEMBAKARAN TERBUAT DARI ABU SEKAM PADI DAN SERBUK BATU TABAS - Sudarsana, I Ketut; Made Budiwati, Ida Ayu; Angga Wijaya, Yohanes (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 1 Januari 2011)
This research was conducted to determine the characteristics of the brick compressive strength and water absorption. The bricks are made by using waste rice husk ash and rock-tabas powder which are added to cement as a glue and mixed with clay and they are left dry without firing. A total of five kinds of mixtures were made with a proportion of total rice husk ash and rock-tabas powder of 30%, 60% of clay and cement as much as 10% mixed with weight ratio. Variations of composition of rice husk ash and rock-tabas powder were made using ratios of 0%: 30%, 7.5%: 22.5%; 15%: 15%, 22.5%: 7.5%, and 30%: 0 %. The samples used are in the form of cubes with a size of 6x6x6 cm. Six-cubes were made form each mixture where 3 of them were used for compressive strength test and the other 3 for water absorption test. Tests conducted at 14 and 28 days. The result showed that the highest compressive strength of bricks without firing was 22.90 kg/cm2 obtained from the mixture I with the percentage of rice husk ash and pulverized tabas of 30%:0% at 28 days, while the lowest water absorption is at 44.03% gained from bricks of mixture V in which the ratio between rice husk ash and rock-tabas powder was 0%:30% at 28 days.
Keywords: rice husk ash, rock-tabas powder, unburnt brick, compressive strength, water absorption.